A Companion to Marsilius of Padua. - Moreno-Riano, Gerson (Brill's companions to the Christian tradition, 2011)
Containing the latest scholarship by an international group of scholars, this book provides an essential guide both to the life and works of Marsilius of Padua as well as to the leading interpretive debates surrounding one of the greatest thinkers of the Latin Middle Ages.